2012
DOI: 10.1246/cl.2012.1397
|View full text |Cite
|
Sign up to set email alerts
|

CeO2-catalyzed Transformations of Nitriles and Amides

Abstract: Recently, cerium oxides have been extensively used as heterogeneous catalysts for green organic reactions. This review describes recent progress in such reactions, with a focus on our studies on pure CeO 2 -catalyzed reactions of nitriles and amides with nucleophiles (H 2 O, alcohols, and amines). Hydration of nitriles to amides in water, one-pot ester synthesis from nitriles and alcohols, one-pot synthesis of N-alkylamides from nitriles with amines, and synthesis of N-alkylamides from amides and amines (trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 76 publications
1
26
0
Order By: Relevance
“…Specifically, we observed good linearity with a positive slope ( ρ =+0.26) (Figure B), which indicates that a transition state in the rate‐limiting step of the phenolysis contains a negative charge at the α‐carbon atom adjacent to the benzene ring. Accordingly, it can be concluded that the nucleophilic addition of the phenoxide species to the activated carbonyl carbon atom of the amide proceeds via a negatively charged transition state, and that this could be the rate‐limiting step of this reaction …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Specifically, we observed good linearity with a positive slope ( ρ =+0.26) (Figure B), which indicates that a transition state in the rate‐limiting step of the phenolysis contains a negative charge at the α‐carbon atom adjacent to the benzene ring. Accordingly, it can be concluded that the nucleophilic addition of the phenoxide species to the activated carbonyl carbon atom of the amide proceeds via a negatively charged transition state, and that this could be the rate‐limiting step of this reaction …”
Section: Resultsmentioning
confidence: 94%
“…The phenolysis of para ‐substituted benzamides with phenol revealed a good relationship between log( k X / k H ) and the Brown–Okamoto parameter ( σ + ) . Specifically, we observed good linearity with a positive slope ( ρ =+0.26) (Figure B), which indicates that a transition state in the rate‐limiting step of the phenolysis contains a negative charge at the α‐carbon atom adjacent to the benzene ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this are picolinic acid or niacin derivate aromatic ester, which are active for apoptosis of human leukaemia cells and rubefacients prodrugs, respectively. 16,17 In nature, protease enzymes can perform peptide bond hydrolysis in proteins through an ATP-dependent process. Inspired by the confined space and active sites of these enzymes (based on transition metals), inorganic artificial systems have been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…For the catalysts containing Zr, the calcination temperature affording the maximum propylene carbonate amount was generally changed to higher one in comparison with pure CeO 2 in spite of the decrease in catalyst surface area. The active sites are thought to be weak acid–base sites on the plain crystalline surface. The active sites can be influenced by the bulk composition of Ce/Zr and more significantly by the surface composition.…”
Section: Introductionmentioning
confidence: 99%